Magnetic Nanocomposites Revolutionize Heavy Metal Adsorption for Environmental Cleanup : Nanokomposit Magnetik Merevolusi Adsorpsi Logam Berat untuk Pembersihan Lingkungan - Waly, Zaynah Salih; Merdas, Samia Mezhr (Academia Open, 2024)
General background: Magnetic nanocomposites have garnered significant attention due to their multifunctional properties, particularly in environmental remediation, where they can be used for the removal of heavy metals from aqueous solutions. Specific background: Polypyrrole (PPy) and poly(p-hydroxyaniline) (P(p-OH An)) are conductive polymers known for their adsorption capabilities, while Fe3O4 nanoparticles exhibit magnetic properties, facilitating separation and recovery. Knowledge gap: Despite the potential of Fe3O4-based composites, few studies have systematically explored the synergistic adsorption properties of PPy and P(p-OH An) in Fe3O4-based nanocomposites under varying environmental conditions. Aims: This study aimed to synthesize and characterize Fe3O4/PPy/P(p-OH An) magnetic nanocomposites and evaluate their adsorption performance under different temperatures and isotherm models. Results: The nanocomposite was synthesized through chemical oxidation polymerization and characterized using FTIR, TEM, AFM, and TGA, confirming its successful formation and nanoscale structure. Adsorption studies indicated an exothermic process, with a decrease in adsorption capacity at higher temperatures. The adsorption data fit the Freundlich isotherm better than the Langmuir model, suggesting heterogeneous surface adsorption. Novelty: This study demonstrates a novel Fe3O4/PPy/P(p-OH An) nanocomposite with superior adsorption properties, showing its potential in heavy metal ion removal and offering an improved understanding of temperature effects on adsorption performance. Implications: The findings underscore the composite’s promise for environmental remediation applications, particularly in water treatment, and suggest further optimization of the adsorption conditions and evaluation of the composite’s reusability for industrial-scale applications. Highlights: Enhanced Adsorption: Fe3O4/PPy nanocomposites offer combined magnetic and polymer adsorption properties. Temperature Sensitivity: Adsorption decreases as temperature rises, indicating exothermic behavior. Surface Interaction: Freundlich isotherm shows adsorption occurs on heterogeneous surfaces. Keywords: Magnetic nanocomposite, Fe3O4, Polypyrrole, Adsorption, Environmental remediation.